Facial Assessment and Injection Guide for Botulinum Toxin and Injectable Hyaluronic Acid Fillers: Focus on the Upper Face. Issue 2 (August 2017) - de Maio, Maurício; Swift, Arthur; Signorini, Massimo; Fagien, Steven
Abstract : Summary: Techniques for the administration of injectable fillers and neuromodulators for facial aesthetic rejuvenation and enhancement continue to evolve. As the number of physicians with limited experience in providing aesthetic treatments expands, the need for guidance and training from more experienced injectors has become apparent. The use of a slow, careful, and methodical injection technique is imperative in all treatment settings and for all facial areas. Constant attention to local anatomy, particularly arteries, veins, and nerve bundles, is critical for minimizing complications. This first article of a three-part series addresses techniques and recommendations for aesthetic treatment of the upper face. Traditionally, the upper face has been considered a basic area for treatment with neuromodulators but an advanced area for treatment with fillers. Injectable fillers may be used for temple volumization, eyebrow shaping, and forehead contouring. Neuromodulators are well suited for diminishing the appearance of dynamic facial lines such as forehead, glabellar, and crow's feet lines, and eyebrow lifting and eye-aperture widening. These techniques may be used independently or together, sequentially or concurrently, to address rejuvenation of individual or multiple facial regions. Overall, this series provides a practical framework of techniques for physicians who desire to perform safe and effective aesthetic treatments using a multimodal approach.